Peran Bank Syariah terhadap Kesadaran Masyarakat Akan Pentingnya Literasi Keuangan Syariah dan Larangan Riba - Risa Nur Aulia; Muhammad Iqbal Fasa; Suharto (Mutanaqishah: Journal of Islamic Banking, 2021)
The financial industry is currently growing quite rapidly. One of the dominant industrial sectors is the Islamic banking industry.The performance assessment of Islamic banking has only focused on the financial aspect. However, there is one most important thing about Islamic banks that is often overlooked, namely compliance with Sharia Compliance. However, along with the development of the era of usury transactions in the banking world today it is increasingly difficult to avoid, including financial institutions that are labeled sharia. One of the causes of the low quantitative development of the Islamic finance industry is the lack of public awareness about financial literacy, especially Islamic financial literacy. In this study using descriptive qualitative research methods. In qualitative research, the main characteristics come from the natural background/reality in society. Therefore, there is a need for literacy of the Indonesian people so that they can assess and choose Islamic financial transactions properly and appropriately. Because financial literacy has been widely recognized as an important skill for individuals facing increasingly complex financial scenarios.